La corresponsabilidad parento - filial en la prestación de alimentos, en el marco de la equidad de derechos - Benavides Yánez, Teófilo Hernán (2015)
This legal research project entitled "STEWARDSHIP PARENTO - SUBSIDIARY IN THE PROVISION OF FOOD UNDER EQUITY RIGHTS" analyzes the relations established around the family in the provision of food; so a reform proposal arises Art. 127, Art. unnumbered 2 of the Code of Childhood and Adolescence, as the law only establishes the responsibility in parent-child care, food, education and protection of children and daughters; in addition to the right to equality before the law, the legal norm refers only to the obligation of the father when he is sued, regardless of the economic situation of the mother failed to observe the principle of the Best Interests of the Child and the constitutional right to developing comprehensive and good living; It requires that the legal standard set obligation equitably, without excluding the person suing should have financial solvency; The inductive method was used because it allows the study of social relations that generates the right to food in the exercise of constitutional rights; deductive method by which the information obtained in the field research and literature considering the approach of general facts on the principle of the best interests and full development of the sons and daughters need of maintenance is interpreted is also used, this It can support the proposed amendment to the said legal norm, and analytical method applied in the doctrinal and legal framework in order to obtain information